A Validated RP-HPLC Stability Method for the Estimation of Chlorthalidone and Its Process-Related Impurities in an API and Tablet Formulation - Chaitali Kharat; Vaishali A. Shirsat; Yogita M. Kodgule; Mandar Kodgule (International Journal of Analytical Chemistry)
Low-dose thiazide and thiazide-like diuretics are widely used as first-line therapy for hypertension. Chlorthalidone, a monosulfamyl diuretic, is frequently prescribed in cases of hypertension and congestive heart failure. In this research paper, an improved reverse-phase HPLC method was developed for the simultaneous identification and quantitation of pharmacopoeia-listed and in-house process- and degradation-related impurities of chlorthalidone in bulk drug and formulations. Chromatographic separation was carried out on a C8 column (250 × 4.6 mm; ‘5 μm particle size) at a flow rate of 1.4 mL/min with a 220 nm detection wavelength. Mobile phase A consisted of buffer solution (diammonium hydrogen orthophosphate (10 mM, pH 5.5)) and methanol at a 65 : 35 ratio (v/v), and mobile phase B consisted of buffer solution and methanol at a 50 : 50 ratio (v/v). The API and formulation were subjected to stress conditions such as acid, alkali, oxidation, thermal, and photolytic conditions. Validation studies for the in-house process impurities were performed for specificity, limit of detection (LOD), limit of quantitation (LOQ), linearity, precision, accuracy, and robustness. Thus, an improved RP-HPLC method capable of good separation of all known and unknown impurities with acceptable resolution and tailing factor was developed.